2020
DOI: 10.1002/jso.26102
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of different metastatic sites for patients with FIGO stage IVB endometrial cancer after surgery: A SEER database analysis

Abstract: Objective This study aimed to investigate the association between different metastatic sites and survival in endometrial cancer (EC) patients with International Federation of Gynecology and Obstetrics (FIGO) stage IVB disease. Methods FIGO stage IVB patients with EC were selected from the surveillance, epidemiology, and end results database. Overall survival (OS) and cause‐specific survival (CSS) were analyzed with Kaplan‐Meier analysis and log‐rank tests. Univariate and multivariate Cox proportional hazard mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
9
2
Order By: Relevance
“…Our analysis found that lung was the most common metastatic organ (46.2%) in EC patients with bone metastasis, compared with other metastatic organs. In contrast to previous studies ( 7 , 22 ), lung metastasis did not remain significant in multivariable analysis. Consistent with previous studies ( 3 , 22 ), liver or brain metastasis were independent predictors of decreased OS and CSS in the multivariable analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our analysis found that lung was the most common metastatic organ (46.2%) in EC patients with bone metastasis, compared with other metastatic organs. In contrast to previous studies ( 7 , 22 ), lung metastasis did not remain significant in multivariable analysis. Consistent with previous studies ( 3 , 22 ), liver or brain metastasis were independent predictors of decreased OS and CSS in the multivariable analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies ( 7 , 22 ), lung metastasis did not remain significant in multivariable analysis. Consistent with previous studies ( 3 , 22 ), liver or brain metastasis were independent predictors of decreased OS and CSS in the multivariable analysis. Therefore, aggressive management of liver and brain metastases may be helpful in prolonging outcomes in EC patients with bone metastasis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For EC, we founded 11 retrospectives studies. In these studies, the median survival time after bone metastases diagnosis ranged from 4.0 to 18.0 months [ 24 , 25 ], with a study that underlined the difference in median survival between patients with Stage III (4 months) and patients with Stage I (17.5 months). The bone metastases occurrence in this cohort of patients ranged from 0.5% [ 27 ] to 15.4% [ 22 ]; this difference could be due to the different number of enrolled patients, which ranged from 403 [ 23 ] to 69,027 in the case of the lowest occurrence [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian cancer Deng et al 2018 [18] NA NA NA Sehouli et al 2013 [19] NA NA NA Zhang et al 2013 [20] CD NA NA NA Zhang et al 2019 [21] NA NA NA Endometrial cancer Guo et al 2020 [22] NA NA NA Hong et al 2021 [23] NA NA NA Kimyon et al 2016 [24] NA NA NA Li et al 2020 [25] NA NA NA Liu et al 2020 [26] NA NA NA Mao et al 2020 [27] NA NA NA McEachron et al 2020 [28] NA NA NA Ouldamer et al 2019 [29] NA NA NA Takeshita et al 2016 [30] NA NA NA Uccella et al 2013 [31] NA NA NA Yoon et al 2014 [32] NA NA NA Uterine sarcoma Bartosh et al 2017 [33] NA NA NA Tirumani et al 2014 [34] NA NA NA Vulvar cancer Prieske et al 2016 [35] NA NA NA Cervical cancer Kanayama et al 2015 [36] NA NA NA Kocaer et al 2018 [37] NA NA NA Lin et al 2018 [38] NA NA NA Makino et al 2016 [39] NA NA NA Manders et al 2018 [40] NA NA NA Matsumiya et al 2016 [41] NA NA NA Nartthanarung et al 2014 [42] NA NA NA Sethi et al 2019 [43] NA NA NA Yin et al 2019 [44] NA NA NA Yoon et al 2013 [45] NA NA NA Zhang et al 2018 [46] NA NA NA Zhang et al 2020 [47] NA NA NA Zhou et al 2020 [48] NA NA NA Acknowledgments: This work was supported by IRCCS Istituto Ortopedico Rizzoli (Ricerca Corrente).…”
Section: Conflicts Of Interestmentioning
confidence: 99%